Mulheres e ideias impressas : projetos feministas de emancipação em periódicos do Rio de Janeiro e Buenos Aires (1852-1855) - Bárbara Figueiredo Souto (2019)
The purpose of the thesis is to compare emancipation feminists’ projects published in the women’s-owned press in Rio de Janeiro and Buenos Aires in the first half of the 1850s. Therefore, I analyzed the Rio de Janeiro newspaper Jornal das Senhoras (1852-1855) and the Buenos Aires periodicals La Camelia (1852) and Album de Señoritas (1854). These journals had a feminist character and, during their circulation, published criticism towards the society at the time, and proposed political and social changes, of which the core interest was the improvement of women’s living conditions. The analysis of the sources was made from the perspectives of Comparative History, Transnational History, Intellectual History, History of the Press and Feminist Studies. The guiding hypothesis of the research was that the patriarchal and conservative pattern of the compared societies – Rio de Janeiro and Buenos Aires – similarly influenced the feminist press in both countries, generating printouts with communicative trajectories. In this sense, I established comparisons and problematized the feminist projects conveyed in the press, besides highlighting agents still understudied by historiography. I was able to conclude that there were more similarities than differences in the emancipation guidelines of the women conveyed in the analyzed printouts, having as a determining element on the trajectories of these works, both in Rio de Janeiro and Buenos Aires, conservatism. Finally, I identified a transnational feminist intellectual, Juana/Joanna Manso, who was a central character in the construction and propagation of feminist ideas in Brazil and Argentina, in the middle of the 19th century.